La danza básica como actividad recreativa para mejorar la coordinación de los estudiantes del octavo al décimo año de la unidad educativa “14 de Octubre-Vicente Rocafuerte, del cantón Pujilí, parroquia la Victoria, en el periodo académico 2014-2015 - Pacheco Quintana, William Paulino (2015)
This research work was carried out in order to know if the Physical Culture Teachers use as recreational material the Basic Dance to improve the students´ coordination from eighth to tenth years of General Basic Education in 14 de October-Vicente Rocafuerte high school, Pujilí canton, La Victoria Parish during the Academic period 2014-2015; determining that teachers predispose students to practice traditional sports to develop their coordination, but not to the practice of basic dance, so these type of activities don´t allow a proper development of their knowledge, skills, values and artistic attitudes….